Development of Edukids Learning Media to Improve Indonesian Vocabulary Mastery of Second Grade Elementary School Students in Enrekang Regency - Amalia Mustafa; Setiawan Edi Wibowo (Department of Special Education, 2025)
This research aimed to (1) produce a digital-based Edukids learning media suitable for improving the Indonesian vocabulary mastery of second grade elementary students in Enrekang Regency, (2) develop a practical learning media, and (3) determine its effectiveness in classroom use. The development process applied the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The product was created by integrating various multimedia objects text, images, animations, audio, videos, and interactive buttons designed to enhance engagement and learning outcomes. The trial was conducted in SD Negeri 33 Enrekang with 33 students as participants. Data collection involved interviews, observations, documentation, and questionnaires, while validation involved three media experts and three material experts. Media validation results achieved an average score of 91.6% (“Very Good”) and material validation 94.4% (“Very Good”). Practicality testing showed teacher responses of 93.3% and student responses of 90.6%, both categorized as “Very Good.” Effectiveness analysis indicated an improvement in average vocabulary mastery scores from 68.32 (pre-test) to 83.30 (post-test), with an N-gain score of 0.58, classified as “Moderate” improvement. These findings confirm that the Edukids learning media is valid, practical, and effective in enhancing Indonesian vocabulary mastery among second grade elementary students, and it holds potential for broader implementation in similar educational contexts.